Evaluating ESG practices and financial impacts: A comprehensive analysis of leading european enterprises under CSR Europe's framework - Gabriela Dubcová; Emil Velinov; Martina Kosikova (Financial Internet Quarterly, 2025)
This study investigates the integration and impact of Environmental, Social, and Governance (ESG) practices within large European enterprises from different industries affiliated with CSR Europe Initiative, which is an influential network championing sustainability. With the impending 2025 requirement for integrated annual reports combining ESG and financial disclosures under the Corporate Sustainability Reporting Directive (CSRD), this research evaluates how these enterprises adhere to and implement ESG principles in their operations. Focusing on a selected group of companies, including financial institutions governed by the Sustainable Finance Disclosure Regulation (SFDR), the study provides a detailed analysis of ESG behaviors using a structured set of seven criteria: Corporate Governance, Responsible Financing, Environmental Behavior, Social Behavior, Quality of Sustainability Reporting, Verification of Institutionalized ESG Strategy, and Annual Turnover. The results emphasize the pivotal influence of environmental strategies on revenue generation, while simultaneously uncovering significant disparities in ESG integration across firms. By addressing a critical gap in the literature regarding the financial implications of ESG engagement, the study contributes nuanced insights into how leading European corporations - specifically those affiliated with the CSR Europe Initiative - can strengthen their sustainability strategies and financial resilience. Furthermore, the findings underscore the necessity of a well-structured ESG framework not only for achieving long-term corporate sustainability, but also for ensuring alignment with evolving European Union regulatory requirements and stakeholder expectations.
Keywords: M14; Q56; 330; ESG Practices; Corporate Governance; CSR behaviour; Integrated Report; Sustainable Business